2015
DOI: 10.1590/0034-737x201562050002
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de clones de seringueira para a região noroeste do Estado de São Paulo

Abstract: As correlações genéticas e fenotípicas foram significativas e positivas entre todos os anos de produção. Para o vigor, a significância dos coeficientes de correlação genotípica e fenotípica diferiram na pré-sangria e na pós-sangria. Pelos valores de produção de borracha observados, os clones IRCA 111 e PB 235 são considerados favorá-veis à recomendação em pequena escala para a região de Votuporanga. Com base nos resultados obtidos, é possível realizar uma seleção precoce para o caráter de produtividade, usando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…Therefore, the observed values indicate good experimental precision. The CV% values in the three experiments were similar to those observed for clones (Alem et al, 2015) and progenies (Verardi et al, 2012) of rubber trees of the same age.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, the observed values indicate good experimental precision. The CV% values in the three experiments were similar to those observed for clones (Alem et al, 2015) and progenies (Verardi et al, 2012) of rubber trees of the same age.…”
Section: Resultssupporting
confidence: 81%
“…The importance of assessing the vigor of rubber tree clones has been highlighted in several studies (Gonçalves et al, 2011;Gouvêa et al, 2012;Silva et al, 2014;Alem, et al, 2015). The genetic improvement program of the Agronomic Institute of Campinas (IAC) has evaluated elite clones of different clone series in distinct regions of São Paulo State.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the conditions of São Paulo plateau Silva et al 19 recorded that the system ½ S d/2 provided the greatest productivity of clone PB 235 and commented that this clone usually exhibit weak response to stimulation, but affirm that in the system ½ S d/7 ET 2.5% yield was superior to the ½ S d/4 ET 2.5% and recommend the system ½ S d /7 ET 2.5% due to absence of tapping panel dryness (TPD) disorder. Under the conditions of the Northwest of Paraná the clone PB 235 responded positively to stimulation in d/7 with a productivity of 1729 kgha -1 yr -1 , as well as the clone IRCA 111 that produced 1603 kgha -1 yr -1 (table 7), both recommended by Alem et al 1 for small-scale plantations in the São Paulo Northwest plateau. Silva et al 19 observed high incidence of TPD disorder in PB 260 clone in ½ S system d/3 ET 2.5% and suggest, to avoid this problem, the system ½ S d/5 ET 2.5% or ½ S d/7 ET 5%.…”
Section: Resultsmentioning
confidence: 86%
“…There are studies that show that vigor (measured by stem perimeter) is considered the most important character to determine the precocity of the clone, allowing the rubber tree producer to have a faster return of its investment, with greater production in the first years of life, which confirm the efficiency of the early tests (Alem et al, 2015). Based on the high correlation between annual perimeter growth and rubber production and observed results, it is possible to predict that selection with this population is possible in young plants with maximum gain and in short time, minimizing the rubber production cycle (Gonçalves et al, 2006;Verardi et al, 2014).…”
Section: Prediction Of Selection Gainsmentioning
confidence: 93%